2017
DOI: 10.1039/c7ra02346d
|View full text |Cite
|
Sign up to set email alerts
|

Integration of heterologous 4-hydroxybenzoic acid transport proteins in Rhodobacter sphaeroides for enhancement of coenzyme Q10production

Abstract: This work provides a novel genetic engineering strategy that improves uptake of extracellular 4-hydroxybenzoic acid by heterologously expressing the membrane transport protein PcaK in R. sphaeroides for enhancement of CoQ10 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although other work has focused on increasing yields of endogenous MK, such as in E. coli and Bacillus subtilis , this is the first metabolic engineering of the synthesis of the entire MK biosynthetic pathway from chorismate and polyprenyl diphosphate in a heterologous host, in this instance using nine genes from E. coli . The synthesis of MK in R. sphaeroides , coupled with the versatile ability to heterologously express integral membrane proteins, , may provide a platform enabling further studies of proteins from recalcitrant or pathogenic organisms (especially those lacking genetic tools) that interact with or incorporate MK into integral membrane proteins, such as the TtRC from T. tepidum , and MenA from M. tuberculosis . This approach could also be used to engineer RCs from green filamentous photosynthetic bacteria such as the thermophile C. aurantiacus for thermostable biophotovoltaic applications, , and possibly RCs and other MK-requiring enzymes encoded in metagenomes from environmental DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Although other work has focused on increasing yields of endogenous MK, such as in E. coli and Bacillus subtilis , this is the first metabolic engineering of the synthesis of the entire MK biosynthetic pathway from chorismate and polyprenyl diphosphate in a heterologous host, in this instance using nine genes from E. coli . The synthesis of MK in R. sphaeroides , coupled with the versatile ability to heterologously express integral membrane proteins, , may provide a platform enabling further studies of proteins from recalcitrant or pathogenic organisms (especially those lacking genetic tools) that interact with or incorporate MK into integral membrane proteins, such as the TtRC from T. tepidum , and MenA from M. tuberculosis . This approach could also be used to engineer RCs from green filamentous photosynthetic bacteria such as the thermophile C. aurantiacus for thermostable biophotovoltaic applications, , and possibly RCs and other MK-requiring enzymes encoded in metagenomes from environmental DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous expression of MFS transporters can improve metabolite production by microbes (41,42). For instance, a system for coenzyme Q 10 production from 4-hydroxybenzoate and glucose using a Rhodobacter strain expressing Corynebacterium or Klebsiella pcaK demonstrated 1.18-to 1.21-fold greater yield than the wild-type Rhodobacter strain (43). Similarly, our laboratory found that pcaK overexpression in a SYK-6-derived strain enhanced PDC production 1.24-fold from protocatechuate (22).…”
mentioning
confidence: 70%
“…In 2017, Qi and co-workers successfully engineered Rhodobacter sphaeroides , a natural producer of CoQ10 by expressing three membrane transport proteins (AcPcaK from Acinetobacter calcoaceticus , KpPcaK from Klebsiella pneumoniae , and CgPcaK from Corynebacterium glutamicum ) involved in the transport of 4-hydroxybenzoic acid, which is a key intermediate in the biosynthesis of CoQ10, therefore improving the production of CoQ10. 297 The same group built on this existing work, 298 and in 2020 they identified a bottle neck in the production of farnesyl pyrophosphate (FPP) 64 (Fig. 13), which is generated from the MEP pathway.…”
Section: Anti-ageing Ingredientsmentioning
confidence: 99%